PAK proteins and YAP-1 signalling downstream of integrin beta-1 in myofibroblasts promote liver fibrosis - Katherine Martin (Nature Portfolio, 2016)
Antifibrotic therapies that target myofibroblast activation are needed to treat chronic liver disease. Here the authors identify an axis of integrin beta-1 expression and Yap-1 and Pak protein signalling that can be interfered with to inhibit myofibroblast function and liver fibrosis in vivo.